The Management of Midline Frontonasal Dermoids. Issue 1 (January 2015) - Moses, Mike A.; Green, Ben C.; Cugno, Sabrina; Hayward, Richard D.; Jeelani, Noor U. Owase; Britto, Jonathan A.; Bulstrode, Neil W.; Dunaway, David J.
<x xml:space="preserve">Abstract</x> Background: The incidence of midline frontonasal dermoid cysts is one in 20, 000 to one in 40, 000. These lesions may have intracranial extension. This is explained by the anatomy and embryology of nasofrontal development. Skin involvement may also be extensive. Incomplete excision frequently leads to recurrence. The authors report their experience and pathway for management of midline dermoids. Methods: Databases were searched to identify patients who had undergone surgery for removal of a dermoid cyst. Preoperative imaging and indications for surgery were reviewed. Cases were grouped according to surgical approach, and outcomes and complications were identified. Results: Fifty-five patients were treated. Magnetic resonance imaging or computed tomography was used to delineate the anatomy, and surgical excision was expedited if there was a history of infection, especially if imaging suggested intracranial extension. Twelve patients were treated endoscopically (one was converted to open). Eleven required transcranial approaches for intracranial extension (20 percent). Of these, one lesion breached the dura. The remaining 32 patients had dermoids excised with an open approach (direct, bicoronal, or rhinoplasty). There were no recurrences in the open group and there was one recurrence in the transcranial group. This was treated by reexcision. Conclusion: Midline dermoid cysts are relatively uncommon. However, knowledge of the pathogenesis of these lesions together with the authors' experience over 15 years has allowed them to develop a protocol-driven approach, with a low incidence of complications. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.